Buring Mouth Syndrome in A Medically Compromised Geriatric Individual- A Case Report and Review of Literature - Shunmugavelu, Karthik; V, Ramya; RN, Mugundan; Hasheer, Shermin; Vijayakumar , Vishali; Manda Balaji , Sridevi; Cynthia, Evangeline (Journal of Dental School, 2021)
Abstract Burning mouth syndrome (BMS) is defined as “intra-oral burning or dysesthetic sensation, recurring daily for more than 2 hours per day for more than 3 months, without clinically evident causative lesions”. It can be associated with related symptoms, such as xerostomia and dysgeusia. The etiology of BMS remains unknown, although a number of local, systemic and psychological factors have been proposed as being of etiopathogenic importance. BMS has been classified into two categories: ‘Primary or essential/idiopathic’ BMS and “Secondary” BMS, primary where the local or systemic causes cannot be identified, and involving peripheral or central neuropathological pathways. While the secondary type is associated with local, systemic or psychological factors. Here we report a case of BMS that was caused due to an underlying gastro esophageal reflux disease (GERD) and also explains about the importance of treating the underlying condition.